Military nursing research : bibliographies - Institute of Medicine (U.S.). Committee on Military Nursing Research (Washington, D.C. : National Academy Press, 1996)
Description for testing purposes.
6 Research in Progress; TRISERVICE NURSING RESEARCH PROGRAM; NATIONAL INSTITUTE OF NURSING RESEARCH; NURSING RESEARCH INITIATIVE OF THE DEPARTMENT OF VETERANS AFFAIRS; Acronyms
Prepared to accompany: The program for research in military nursing: progress and future direction. 1996.
Includes bibliographical references.
Print version record.
eBooks on EBSCOhost
Keywords: Military nursing -- Abstracts; Military nursing; Nursing -- Research; Military Nursing; Nursing Research; Soins infirmiers militaires -- Résumés analytiques; Soins infirmiers militaires; Soins infirmiers -- Recherche; HISTORY -- Military -- Biological & Chemical Warfare; Nursing -- Research; Military nursing; Abstracts; headings; abstracts (summaries); Abstracts; Abstracts; Résumés analytiques